(untitled) (Scottish Historical and Archaeological Internet Reports, 2003)
While the insertion of the cremation vessel into a pit in the inverted position is typical of cinerary urns of this type at this type, its context of deposition within a boulder shelter, is more unusual though not entirely without parallel.